2021
DOI: 10.1111/bcp.14806
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus dose, blood concentrations and acute nephrotoxicity, but not CYP3A5/ABCB1 genetics, are associated with allograft tacrolimus concentrations in renal transplant recipients

Abstract: Aims Long‐term use of the immunosuppressant tacrolimus is limited by nephrotoxicity. Following renal transplantation, the risk of nephrotoxicity may be determined more by allograft than by blood tacrolimus concentrations, and thus may be affected by donor CYP3A5 and ABCB1 genetics. Little is known regarding factors that determine tacrolimus intrarenal exposure. Methods This study investigated the relationship between trough blood (C0Blood) and allograft (CGraft) tacrolimus concentrations and tacrolimus dose, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 48 publications
(60 reference statements)
2
24
1
1
Order By: Relevance
“…In contrast to recently published results [27], we have observed no significant correlation between daily doses of tacrolimus and graft concentration (p = 0.457 and p = 0.424, respectively). Similarly, a weak correlation between C 0 blood and tissue concentration was displayed both in kidney and in liver organs (p = 0.151; p = 0.391).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to recently published results [27], we have observed no significant correlation between daily doses of tacrolimus and graft concentration (p = 0.457 and p = 0.424, respectively). Similarly, a weak correlation between C 0 blood and tissue concentration was displayed both in kidney and in liver organs (p = 0.151; p = 0.391).…”
Section: Discussioncontrasting
confidence: 99%
“…By assessing the results obtained in this study with previous ones sparingly found in the literature, excluding cases of isolation from other matrices [21][22][23][24][25][26][27][28], it has to be stated that a low value of TAC concentrations in the tissue of transplanted organs may favor the risk of occurrence the acute rejection episodes. We are convinced that other matrices used in TAC concentration determination could be more complicated, for example, bile [29] or urine.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ABCB1 CT c.3435 predicts reduced P-gp functionality at the graft level and thus could theoretically have participated in the intraparenchymal accumulation of tacrolimus (Hauser et al, 2005). Although still controversial in the literature, this variant has been associated with decreased renal function at 1, 3 and 6 months and 1 year after transplantation (p < 0.01) when the graft carries the CT or TT genotypes compared with CC (Tavira et al, 2015;Sallustio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies ( Table 1A ) have recently investigated potential relationships between renal graft tacrolimus concentrations and clinical outcomes ( Zhang et al, 2020 ; Sallustio et al, 2021 ). In 52 renal transplant recipients there was no difference in renal tacrolimus concentrations between patients with or without histologically classified subclinical acute rejection at 3 months or 1 year post transplantation ( Zhang et al, 2020 ).…”
Section: Allograft Tacrolimus Concentrationsmentioning
confidence: 99%